Safety Evaluation of Syzygium jambolanum on the Development of Zebrafish Embryos - Sharma, Mahima; Prajapati, Suneel; Kumar, Arun; Tripathi, Ashish; Kumar, GV Narasimha; Gupta, Pankaj (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Gestational diabetes mellitus, a hyperglycaemic condition that develops at the time of pregnancy, causes approximately 7% of complications during pregnancies world wide. Syzygium jambolanum has been proved clinically for the management of diabetes mellitus and is being prescribed for the management of diabetes in pregnant women. Objectives: This study has been designed to evaluate the safety of Syzygium jambolanum mother tincture on the development of zebrafish embryos. Materials and Methods: Zebrafish embryos were exposed to 1%, 5% and 10% of Syzygium jambolanum mother tincture with the same concentration of alcohol. Observations like mortality, hatching at 24, 48 and 72 hr post fertilization and yolk sac edema, length, eye width, pericardial edema and heart rate were recorded at 72 hr post fertilization. The locomotor activity was recorded at 7 day post fertilization. Results: Results showed that mortality in zebrafish embryos with the treatment of Syzygium jambolanum mother tincture at 10% could be due to alcohol as similar results were observed with 10% alcohol also. Moreover, changes observed in heart beat in embryos with the treatment of alcohol at different concentration were reduced by the Syzygium jambolanum indicating its possible protective role in cardiac parameters. Conclusion: Results suggest the safety of Syzygium jambolanum mother tincture at low concentrations (1% and 5%) on development of zebrafish embryos. The embryo toxicity induced by 10% concentration of Syzygium jambolanum may be attributed to the ethanol. Further developmental toxicity studies on animals need to be carried out to validate the results obtained followed by clinical validation.
Keywords: Danio rerio; Development toxicity; Embryo toxicity; Syzygium jambolanum; Zebrafish